Representação política e movimentos sociais negros no brasil: um estudo sobre as experiências de comunicação online de ativistas eentidades - Alicianne Gonçalves de Oliveira (2017)
This research, based on current discussions on the role of social movements to expand democratic processes, analyzes the relationship between online communication developed by black social movements and non-electoral political representation in Brazil. It investigates, through comparative analysis, four experiences of online communication of two types of actors entities and entrepreneurs of the black cause. Drawing on texts published by these agents, from 2011 to 2013, regarding the debate on the Quotas Law (nº 12.711/2012), the analysis focuses on central aspects of these actors action: provision of plurality and claims for inclusion. Our theoretical and methodological proposal recommends a dialogue between two important theoretical currents about political representation one based on the pragmatism of Michael Saward and the other influenced by the discursive ethics of Habermas. We assume that the social movements online communication as well as the way they exercise representation are linked to other aspects of political action, encompassing forms of strategy, organization and decision-making. In addition, this dissertation is inspired on the systemic perspective of deliberation to better understand the plurality of actors involved in the representative process. This perspective helps paying closer attention to the diversity discourses and perspectives put forth by a social movement. The methodology is based on indicators of the cultures of movements strategy, organization, decision-making, and online communication, as developed by Anastasia Kavada. Our methodology is based also on the Method of Claims Analysis, as proposed by Koopmans and Statham, as well as on the Discourse Quality Index (DQI), as developed by Steiner and his colleagues. While the former approach is directly linked to the theory of discursive representation, the latter is connected to deliberative studies. Our comparative analysis on the selected actor online communication is organized around three central questions: (a) demands prioritized by these agents; (b) strategies, and (c) communicational characteristics. Our findings show that distinct types of actor, which are embedded in distinct cultures, tend to use digital platforms in different ways. Diverse communication experiences affect also the nature of the representative process. In particular, our results reveal how the representation process is shaped by entities and entrepreneurs of the black cause, by means of their discursive flows in online communication. Thus, this study helps increasing our understanding about the social movements communicative practices, always linked to political choices, as essential means for building therepresentative dynamics.